Early Life Circumstances and the Health of Older Adults: A Research Note - Xi Chen (Institute of Labor Economics (IZA), 2022)
This paper reviews the latest evidence of the effects of early life circumstances on old-age health, distinguishing in utero exposures from childhood exposures to a wide range of environments. We then leverage the growing number of studies of the impact of the Great Chinese Famine (1959-1961) on the health of older adults to perform a meta-analysis and discuss potential mechanisms. Recent studies assembling multiple domains of early life circumstances are evaluated to better understand how various circumstances may coalesce and manifest in shaping long-term health.
Keywords: I14; J14; J13; I18; 330; early life circumstances; old-age health; famine; long-term health; meta-analysis; China